Penyuluhan “Adu Sitomas” (Adminkes UAM Bersinergi Membentuk Pelopor Remaja Anti Stunting) di MA Darussalam Jombang - Dwike Primadita Rosanti; Firda Diah Utami; Alya Aqillah (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
The “Adu Sitomas” counseling held at MA Darussalam Jombang aims to improve students' knowledge, attitudes, and behavioral practices related to stunting. Stunting is a serious health problem that affects the physical growth and cognitive development of children. Through this program, students are provided with relevant information on the causes, impacts, and ways to prevent stunting. The results showed a significant increase in students' understanding, with the level of knowledge increasing from 60% to 90% after the counseling. Positive attitudes towards the issue of stunting also increased from 40% to 75%, while the practice of related behaviors increased from 70% to 90%. Student engagement in discussions reached 90%, reflecting their enthusiasm to learn more. These findings emphasize the importance of collaboration between educational institutions and public health programs in stunting prevention efforts, as well as the potential of students as agents of change in supporting the health of future generations.